Is the process of successful sexual aging different in older partnered and non-partnered adults? - Aleksandar Štulhofer; Azra Tafro; Laura Pietras; Ivan Landripet; Goran Koletić (PLoS ONE, 2026)
As populations in the Western world age, interest in the sexual health and well-being of older adults has grown substantially, yet positive models of sexual aging remain underexplored—especially across diverse relational contexts. To address this gap, the Successful Sexual Aging (SSA) model was recently proposed. This model conceptualizes positive sexual aging as a dynamic process involving three interrelated psychosocial domains: acceptance of physical and sexual changes, adaptation to those changes, and the presence of opportunities for sexual expression. These domains were operationalized as a latent construct, which was validated and explored for culture-specific elements in partnered older adults. Given the importance of a close partnership for older adults’ sexuality, but also the fact that many older adults, women in particular, are non-partnered, the current study focused on the assessment of differences in positive sexual aging between partnered and non-partnered older German ( N = 1,328, M age = 69.2) and Croatian adults ( N = 301, M age = 68.8). Using measurement invariance testing and a network analytic approach, we identified important differences in reported obstacles to sexual expression between partnered and non-partnered older adults, and the robustness (connectivity) of the network of SSA-indicating items. Overall, SSA seemed to be somewhat more difficult for older non-partnered adults compared to their partnered peers. Although the 9-item measure of SSA can be used to reliably assess the process of sexual aging in both partnered and non-partnered older individuals, direct comparisons should be avoided due to partnership-specific properties of positive sexual aging.